Intermittent energy restriction and risk of physician-diagnosed diabetes progression: a propensity-weighted real-world cohort study - Xiao, Zhiyong; Zhou, Xu; Yang, Dongliang; Lai, Xihu; Zhang, Yewu; Wu, Ruiyu; Wang, Huiqing; Zhou, Jiali; Yang, Xiao; Xu, Feng; Luo, Wu; Chen, Xuan; et al. (Frontiers in Nutrition, 2026)
BackgroundIntermittent energy restriction (IER) shows metabolic promise, but real-world evidence for its impact on clinically meaningful outcomes is lacking. This study evaluated the effect of IER on a novel composite endpoint of early, physician-diagnosed diabetes progression (PDDP), which includes microvascular complications (retinopathy, nephropathy, neuropathy), acute metabolic decompensation (diabetic ketoacidosis, hyperosmolar hyperglycemic state), and peripheral arterial disease.Materials and methodsIn a large real-world retrospective cohort study, 1,069 participants following a structured 5:10 IER regimen were compared with 1,099 controls. The primary outcome was the incidence of PDDP, a composite of the progression of diabetes-related events diagnosed by clinical doctors. Secondary outcomes included fasting plasma glucose (FPG) change and diabetes medication reduction. Inverse probability weighting (IPW) and multivariate models were used to control for confounders. A sensitivity analysis was restricted to patients without PDDP at baseline (n = 1,788).ResultsThe IER group demonstrated a substantially lower incidence of PDDP compared to controls (2% vs. 10%; p < 0.001). After IPW adjustment, the IER cohort demonstrated a significantly lower incidence of PDDP (Estimate: −0.09; 95% CI: −0.12 to −0.07; p < 0.001), and a greater reduction in antidiabetic medication use (OR: 6.26; 95% CI: 5.61 to 6.99; p < 0.001), no statistically significant difference in FPG change was detected between groups (Estimate: −0.07; 95% CI: −0.46 to 0.32; p = 0.740). Sensitivity analysis confirmed the robustness of these benefits in the population without PDDP at baseline.ConclusionIn a real-world setting, IER was associated with a dramatically lower risk of PDDP, independent of its glucose-lowering effect. These findings position IER as a potent, scalable non-pharmacological strategy to improve patient-centered outcomes in diabetes care.